Pemanfaatan pupuk cair limbah sayur dan buah pada kacang tanah (Arachis hypogea L.) di dataran rendah Kota Palopo - Nining Triani Thamrin; Rahman Hairuddin; Eka Sudartik (Fakultas Pertanian Universitas Ichsan Gorontalo, 2019)
This study aims to determine the effect and concentration of liquid fertilizer prepared from fruit and vegetable waste on the growth and yield of peanut plants. This research was carried out in the Experimental Field of the Faculty of Agriculture, University of Cokroaminoto Palopo, Jalan Lamaranginang, Batupasi Village, Wara Utara District, Palopo City. The experimental method used was a randomized block design (RBD) consisting of 5 treatments and 4 replications to comprise 20 experimental units. Each experimental unit consisted of 2 plant units so that there were 40 plant samples. The parameters observed were plant height, flowering age, root length, pod weight and the number of seeds. The results showed that the application of liquid fertilizer prepared from fruit and vegetable waste had a significant effect on the growth and yield of peanut plants. The effective concentration of fruit and vegetable waste liquid fertilizer was P4 (250 mL.L-1 water) that produced the best plant height with an average value of 20.93 cm, the average age of flowering was 33 days, the average root length was 4.49 cm, and the best average pods (22.77 grams), while a concentration of 200 mL.L-1 water (P3) produced the best average number of seeds (340.25 seeds).